2018
DOI: 10.1080/09537104.2018.1479519
|View full text |Cite
|
Sign up to set email alerts
|

Individual long-term variation of platelet reactivity in patients with dual antiplatelet therapy after myocardial infarction

Abstract: There is a large inter-individual variation in response to clopidogrel treatment, and previous studies have indicated higher risk of thrombotic events in those with high residual platelet reactivity (HPR). Less is known about individual variation over time. The aim of this prospective cohort study was to investigate intra-individual variation in platelet reactivity. Platelet aggregation in whole blood was assessed in 77 patients, at 3 days, 8 days and 6 months after admission for acute myocardial infarction an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 29 publications
(40 reference statements)
0
4
0
5
Order By: Relevance
“…37 The high rates of longitudinal intraindividual variation in clopidogrel responder status might weaken the predictive information of platelet function testing. 38,39 Of note, some studies have found that LRC was accompanied by the presence of resistance to aspirin. 40 In this study, there was no significant difference in the proportion of aspirin resistance between different groups.…”
Section: Discussionmentioning
confidence: 99%
“…37 The high rates of longitudinal intraindividual variation in clopidogrel responder status might weaken the predictive information of platelet function testing. 38,39 Of note, some studies have found that LRC was accompanied by the presence of resistance to aspirin. 40 In this study, there was no significant difference in the proportion of aspirin resistance between different groups.…”
Section: Discussionmentioning
confidence: 99%
“…В нашем исследовании мы выявили динамику частоты встречаемости ВОРТ на ДАТТ. Динамику активности тромбоцитов и повышение спонтанной агрегации тромбоцитов в течение 14 дней -1 месяца после ИМ по сравнению с исходными значениями наблюдали и другие авторы [20][21][22][23][24].…”
Section: таблица 5 данные общего анализа крови и морфометрические пок...unclassified
“…Динамику активности тромбоцитов и повышение спонтанной агрегации тромбоцитов в течение 14 дней -1 месяца после ИМ по сравнению с исходными значениями наблюдали и другие авторы [14][15][16][17][18].…”
Section: таблица 2 показатели импедансной агрегометрии в подгруппах с...unclassified